God grew tired of us : a memoir - Dau, John Bul.; Sweeney, Michael S. (Washington, DC : National Geographic, 2007)
Presents the plight of young, male Sudanese refugees, known as "lost boys," being displaced to foreign countries due to civil war in their homeland. The film tells the story of three of the lost boys who struggled to come to the United States for a better life, while still attempting to assist the family and friends they have left behind.
Includes bibliographical references (p. [291]).
Keywords: Dau, John Bul; Refugees -- Sudan -- Biography; Sudan -- History -- Civil War, 1983-2005.; Sudan -- History -- 1983- , Civil War